ANALISIS TOTAL PRODUCTIVE MAINTENANCE (TPM) PADA MESIN EKSTRUDER DI PT VOLEX BATAM - Zulhamdi, Tommy; Sirait, Ganda (Computer Science and Industrial Engineering, 2025)
At PT Volex Batam, the ekstruder machine is an integral part of the cable production process, used for the extrusion of cable insulation and protective layers. This machine plays a vital role in production; however, during the period of September 2024 to February 2025, a total downtime of approximately 194.4 hours was recorded, which disrupted production and caused delivery delays. This study aims to measure the effectiveness level of the ekstruder machine using the Overall Equipment Effectiveness (OEE) indicator and to identify the factors contributing to the high frequency of machine failures. The methods used in this research are OEE calculation and Six Big Losses analysis. The results show an average OEE value of 73%, which is below the ideal standard of ≥85%. The OEE components include availability at 88%, performance rate at 91%, and quality rate at 90%. The major losses come from equipment failure losses (9.6%), defect losses (8.8%), and idling & minor stoppages (5.1%). Based on the fishbone analysis, four main causes were identified: operator skills, inconsistent SOPs, worn-out machine components, and unstable environmental conditions. The proposed improvements focus on operator training, the implementation of preventive maintenance, and improvement of the working environment.